2016
DOI: 10.1007/s00056-016-0060-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sabbagh Universal Spring 2 fixed functional appliance on class II/1 patients at their postpubertal-peak growth period compared with the extraction method

Abstract: SUS 2 corrected class II/1 malocclusion of patients in the postpubertal growth period by inhibiting the maxilla's forward growth, advancing the mandible, decreasing the nasolabial and interincisal angles, proclining the incisors, increasing the facial height, and clockwise rotation of the occlusal plane. Extraction reduced the interincisal angle and protruded the lower incisors. However, it did not change the soft tissue thickness and did not cause a clockwise rotation in the occlusal plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
3
3
0
Order By: Relevance
“…This change was a result of the forward position of the mandibular base using the Powerscope appliance that brought the position of point B forward. That was in agreement with the results of Powerscope studies ((23,14,19,28,16,17) in addition to the following studies (20,25,26,27) using MARA, Churro Jumper, FNFS, JJ, and SUS 2 appliances. On the contrary, studies (11,24) used the Powerscope appliance, and also studies (21,22) using FFRD and TFBC showed no significant change happened in the anteroposterior position of the mandible.…”
Section: Changes In the Skeletal Measurementssupporting
confidence: 91%
See 1 more Smart Citation
“…This change was a result of the forward position of the mandibular base using the Powerscope appliance that brought the position of point B forward. That was in agreement with the results of Powerscope studies ((23,14,19,28,16,17) in addition to the following studies (20,25,26,27) using MARA, Churro Jumper, FNFS, JJ, and SUS 2 appliances. On the contrary, studies (11,24) used the Powerscope appliance, and also studies (21,22) using FFRD and TFBC showed no significant change happened in the anteroposterior position of the mandible.…”
Section: Changes In the Skeletal Measurementssupporting
confidence: 91%
“…There was a statistically significant (P ≤ 0.05) decrease in SNA angle which indicated the effect of Powerscope appliance on the restriction of the maxillary base that was agreed with the results reported by other Powerscope studies (23,24,16) in addition to studies (25,26,27) using Churro Jumper, Forsus Nitinol Flat Spring (FNFS), Jasper Jumper (JJ) and Sabbagh Universal Spring 2 (SUS 2) appliances. On the contrary, studies (11,14,18,19,17) using Powerscope appliance and other studies (20,21,22) using Mandibular Anterior Repositioning Appliance (MARA), Forsus Fatigue Resistant Device (FFRD) and Twin Force Bite Corrector (TFBC) appliances showed no statistically significant changes happened to SNA angle and consequently to the maxilla.…”
Section: Changes In the Skeletal Measurementssupporting
confidence: 89%
“…Our study also is surrounded by the same controversies as we cannot delineate the effect of skeletal changes to see any secondary and favorable dentoalveolar or soft-tissue changes. Although the skeletal changes are not so obvious, the overall soft-tissue results are acceptable due to the secondary effects seen on the dentoalveolar components[ 14 15 16 17 18 19 20 ] The criteria for diagnosing a typical Class II malocclusion used in this study The pubertal growth assessment done may be controversial as no single method is reliable enough. [ 8 9 10 11 12 13 ] …”
Section: Discussionmentioning
confidence: 99%
“…Our study also is surrounded by the same controversies as we cannot delineate the effect of skeletal changes to see any secondary and favorable dentoalveolar or soft-tissue changes. Although the skeletal changes are not so obvious, the overall soft-tissue results are acceptable due to the secondary effects seen on the dentoalveolar components[ 14 15 16 17 18 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Hemmatpour et al [ 26 ], the authors demonstrated that the nonextraction method significantly increased the N′-Gn′ ( p = 0.029), N′NsPog′ ( n = 0.002), Pog-Pog′ ( p = 0.03), and SS-Ls ( p = 0.001), compared to the extraction group.…”
Section: Resultsmentioning
confidence: 99%